TNF-alpha protects from exacerbated autoinflammatory response in mouse model of experimental autoimmune myocarditis. (25th November 2020) - Rolski, F; Weglarczyk, K; Pelczar, P; Siedlar, M; Ludewig, B; Kania, G; Blyszczuk, P
Abstract: Background: Myocarditis is an inflammatory heart disease and heart-specific autoimmunity plays an important role in development and progression of the disease. TNF-α is a potent pro-inflammatory cytokine implicated in pathogenesis in many inflammatory diseases. Unexpectedly, clinical studies showed that high dose anti-TNF-α therapy increased hospitalization and mortality of heart failure patients. Purpose: To elucidate the role of TNF-α in heart-specific autoimmunity and in activation of cardiac microvascular endothelial cells in autoimmune response. Methods: Experimental autoimmune myocarditis (EAM) was induced in BALB/c mice by immunization with α-myosin heavy chain peptide (α-MyHC) together with complete Freund's adjuvant. Development of myocarditis in the absence of adjuvant was analysed in TCR-M mice, which CD4+ T cells expressed transgenic T cell receptor recognizing α-MyHC. The role of TNF-α was addressed using haploinsufficient Tnf+/−, knockout Tnf−/− and TCR-M x Tnf+/− mice. Effects of antigen-dependent T cell response on cardiac microvascular endothelial cell (cMVEC) activation were assessed by flow cytometry, immunoblotting and leukocyte-endothelium adhesion assay. Inflammatory cells were phenotyped using flow cytometry, cytokine production was measured by ELISA. Results: EAM induction resulted in reduced prevalence of myocarditis in Tnf+/− and Tnf−/− comparing wild-type mice at day 21 after disease induction. However, Tnf+/− and Tnf−/− mice that developed myocarditis showed higher severity of the disease than wild-type controls. On the other hand, TCR-M x Tnf+/− mice showed exacerbated myocarditis at age of 2 months and were characterized by increased mortality comparing with TCR-M controls. TCR-M Tnf+/− mice showed increased total number of cardiac infiltrates compared to TCR-M controls, but no difference in myeloid subsets were observed. In contrast, Tnf+/− and Tnf−/− mice showed significantly increased percentage of T effector cells in spleens and blood in both myocarditis models. Stimulation with rTNF-α induced expression of intercellular adhesion molecules (ICAM1, VCAM1 and P-selectin) on cMVECs, which was associated with increased ability to bind leukocytes under shear flow conditions. TNF-α deficiency had, however, no impact on antigen-specific activation and proliferation of T-cells. Medium conditioned of antigen-activated wild-type, Tnf+/− and Tnf−/− CD4+ T cells showed similar cMVEC activation measured by increased expression of intercellular adhesion molecules and binding of leukocytes under shear flow condition. Furthermore, Tnf+/− and Tnf−/m- myeloid cells showed increased production of IL-6. Conclusions: Our data suggest that TNF-α protects the heart from excessive autoimmune reaction by suppressing expansion of autoreactive effector T cells. Thus, this study uncovers a cardioprotective role of proinflammatory TNF-α and potentially can explain the deleterious effect of high dose anti-TNF-α therapy in heart failure patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The National Science Centre Poland